The Effect Of Perceived Of Usefulness And Perceived Ease Of Use On Online Purchasing Behavior With E-Wallet User Satisfaction As Intervening : Study On Millennials As E-Wallet Users In Guntur District, Demak Regency - Eka Puji Lestari; Firdaus Firdaus; Nurhayati Nurhayati; Irmaya Yulianti; Tengku Muhammad Ikhfan; Endah Ratnasari (International Journal of Economics, Management and Accounting, 2024)
This research is a type of quantitative research with non-probability methods. The population of this study is unknown, so it uses the Lemeshow formula, and the number of samples used is 100 respondents. The data collection technique used convenience sampling with the distribution of questionnaires that had been tested for the validity and reliability of the data. The data analysis method used consisted of descriptive analysis, evaluation of the outer model, evaluation of the inner model, and evaluation of indirect effects (mediation). The data analysis tool in this study uses the SmartPLS 3.0 software. The results of this study indicate that perceived of usefulness has a positive and insignificant effect on online purchasing behavior with a significance value of 1.326 < 1.96. Perceived of usefulness has a positive and significant effect on e-wallet user satisfaction with a significance value of 2.685 < 1.96. E-wallet user satisfaction has a positive and significant effect on online purchasing behavior with a significance value of 3.794 < 1.96. Perceived ease of use has a positive and significant effect on e-wallet user satisfaction with a significance value of 8.397 < 1.96. E-wallet user satisfaction has a positive and significant effect in mediating the relationship between perceived of usefulness and online purchasing behavior with a significance value of 2.685 < 1.96.